RETRACTED: Pemasaran UMKM Dodol Ketan Di Kecamatan Kampung Melayu Kota Bengkulu - Ida Anggriani; Geni Rama Junita; Indah Mardiana; Akbar Kurniawan; Rian Septiandre (Jurnal Dehasen Untuk Negeri, 2023)
RETRACTED NOTICE Following up on the review of articles published in the Dehasen Untuk Neger Journal carefully, carefully, and considering the article entitled "Pemasaran UMKM Dodol Ketan Di Kecamatan Kampung Melayu Kota Bengkulu" Vol 2 No 1 (2023), DOI: https://doi.org/10.37676/jdun.v2i1.2932 This paper was found to violate the Dehasen Untuk Negeri Journal Publication principles and has been withdrawn.This article has been published in the journal Dehasen Mengabdi and the letter of revocation of the article is attached in a PDF.The document and its contents have been removed from the Dehasen Untuk Neger Journal, and reasonable efforts should be made to remove all references to this article.